The Influence of Online Customer Review, Flash Sale, and Celebrity Endorsement on the Decision to buy Facetology Sunscreen on Jakarta Marketplace Consumers - Keisya Putri Kadinda; Tafiprios (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study analyzez the influence of online customer reviews, flash sales, and celebrity endorsements on purchasing decisions for Facetology sunscreen products in Jakarta. The research method used is a quantitative approach with causal research type. Data were collected through distributing qustionnaires to 210 respondents who are Facetology Sunscreen consumers in the Jakarta area and analyzed using the Partial Least Square (SmartPLS) technique. And a survey on users, the result of the study showed that Online Customer Review, Flash Sale, and Celebrity Endorsements have a significant influence on Purchasing Decisions.